PENGARUH TEPUNG JAMUR TIRAM (PLEUROTUS OSTREATUS) TERHADAP PENURUNAN GLUKOSA DARAH MENCIT (MUS MUSCULUS) - Eky Rakhmawati, Rina Vitdiawati, Sri Wijayanti Wijayanti (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
The research is aimed at finding whether tiram mushroom powder can decrease thedegree of glucose content and also finding the most effective concentration of tirammushroom powder which can decrease the degree of glucose content in the blood stream ofrat (Mus musculus).This research used rats as the trial unit and tiram mushroom powder as the additivesubstance. The method used was Aloxan Method. Five mg/ml of aloxan was given forcibly toincrease the glucose content in the blood stream. There were 5 (five) cages with 8 (eight)rats each, which means there were 5 (five) treatments. The first cage is the control group (K)as a placebo, the second cage (P1) is for the first treatment with 5% of tiram mushroompowder, the third cage (P3) is for the second treatment with 10% of tiram mushroom powder,the fourth cage (P3) is for the third treatment with 15% of tiram mushroom powder, and thefifth cage (P4) is for the fourth treatment with 20% of tiram mushroom powder. The datawere collected after 24 hours when aloxan was given and on the tenth day of treatment. Thedata were processed with One-way ANNOVA Test to reveal the difference between the controlgroup and treatment groups. When there was a significant difference between the controlgroup and treatment groups, Dunncan Test as an advanced test had to be done to comparethe control group with each of the treatment groups.The results of this research indicated that tiram mushroom powder was capable oflowering the glucose content in the blood stream. One-way ANNOVA showed 0.006 whichwas so far below the error degree (p0.05) which means that the influence of tiram mushroompowder was so significant to decrease the glucose content in the blood stream. DunncanTest indicated no significance between all the treatment groups (p0.05).Keywords : rat (Mus musculus), tiram mushroom (Pleurotus ostreatus), glucose content